1993
DOI: 10.1007/bf00755601
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of adrenal cell functions by cadmium salts. 1. Cadmium chloride effects on basal and ACTH-stimulated steroidogenesis

Abstract: Cultured Y-1 mouse adrenal tumor cells, which secrete 20-alpha-hydroxy-4-pregnen-3-one (20-DHP), were used to investigate the acute nonlethal effects of incremental cadmium chloride (CdCl2) concentrations on basal and maximally stimulated steroid secretion. In addition, cumulative CdCl2 effects during 4-hr incubations, effect reversibility, and viability were determined. Cells were incubated in 1 ml serum-free Eagle's Minimal Essential Medium (FMEM) with or without 0.5 IU (ca. 1.5 microM) adrenocorticotropin (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…1). Although Cd 2ϩ may be cytotoxic at high dosage (50,51), in these experiments Cd 2ϩ did not impair two crucial functions of wild-type AtT-20 cells: prohormone processing (Figs. 3-6) and regulated secretion (Fig.…”
Section: Discussionmentioning
confidence: 72%
“…1). Although Cd 2ϩ may be cytotoxic at high dosage (50,51), in these experiments Cd 2ϩ did not impair two crucial functions of wild-type AtT-20 cells: prohormone processing (Figs. 3-6) and regulated secretion (Fig.…”
Section: Discussionmentioning
confidence: 72%
“…The specific cellular mechanisms responsible for this endocrine disruption are not yet understood. Xenobiotics can directly alter the HPI axis by cytotoxic effects (Ilan and Yaron 1983), they may interfere with the bioactivity of ACTH (Bestervelt et al 1993), or they may inhibit the steroidogenic pathways in adrenal cells (Mgbonyebi et al 1993). Increased clearance rates of plasma cortisol could also explain the lower cortisol levels in chronically stressed fish (Schreck et al 1985).…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that cadmium interfered with normal gonadal function, as a significant reduction was observed in hormonal levels in vivo (Piasek and Laskey, 1994;Paksy et al, 1997;Piasek et al, 2002;Sen Gupta et al, 2004a) as well as in vitro (Mgbonyebi et al, 1998;Piasek and Laskey, 1999;Piasek et al, 2002). Cadmium has also been shown to stimulate the synthesis of ovarian luteal progesterone at low doses; however, at high doses, the synthesis was inhibited (Henson and Chedrese, 2004).…”
Section: Introductionmentioning
confidence: 99%